2021
DOI: 10.1111/ejn.15210
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐induced secretion of semaphorin 3A mediates learning

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Semaphorins have important functions in neurodevelopment, including guiding axonal growth, dendritic arborization, and regulating synaptic formation 65 . Activity‐induced secretion of SEMA3A was found to mediate contextual memory formation by increasing AMPA (α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid) receptor expression in hippocampal synapses via the NRP‐1–PLXNA4–SEMA3A complex 66 . Together, our pathway analyses suggest that reduced VEC expression in AD brains is potentially associated with cognitive impairment through reduced SEMA3A ‐mediated hippocampal learning.…”
Section: Resultsmentioning
confidence: 99%
“…Semaphorins have important functions in neurodevelopment, including guiding axonal growth, dendritic arborization, and regulating synaptic formation 65 . Activity‐induced secretion of SEMA3A was found to mediate contextual memory formation by increasing AMPA (α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid) receptor expression in hippocampal synapses via the NRP‐1–PLXNA4–SEMA3A complex 66 . Together, our pathway analyses suggest that reduced VEC expression in AD brains is potentially associated with cognitive impairment through reduced SEMA3A ‐mediated hippocampal learning.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the established function for the semaphorins and their receptors (Nrp and plexin family members) in neurodevelopment (32,58), only a few lines of evidence demonstrated their involvement in homeostatic and Hebbian forms of plasticity in the adult hippocampus (31,50,59,60). Notably, Nrp1 is localised at synapses of the adult rat hippocampus (60) and secreted semaphorins acting on the sema-Nrp-plexin complex modulate synaptic connectivity in granule cells of dentate gyrus and pyramidal neurons of CA1 (60) as well as AMPA receptor trafficking in CA3-CA1 synapses (50). The present study adds to this body of literature by demonstrating that Nrp1 is required for the formation of hippocampal long-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the confirmation with two independent shRNA sequences, we focused on Nrp1 which has been shown to be regulated by enriched environment exposure(57) and within dentate gyrus memory engrams(48). Besides the established function for the semaphorins and their receptors (Nrp and plexin family members) in neurodevelopment(32,58), only a few lines of evidence demonstrated their involvement in homeostatic and Hebbian forms of plasticity in the adult hippocampus(31,50,59,60). Notably, Nrp1 is localised at synapses of the adult rat hippocampus(60) and secreted semaphorins acting on the sema-Nrp-plexin complex modulate synaptic connectivity in granule cells of dentate gyrus and pyramidal neurons of CA1(60) as well as AMPA receptor trafficking in CA3-CA1 synapses(50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, each Sema3 molecule differentially and precisely regulates various cognitive function through its speci c receptor complex. A recent study reported that Sema3A-plexinA4 signaling mediated fear learning and memory through decreased phosphorylation of serine 522 of CRMP2 [75]. Future studies are needed to delineate how Sema3A in uences CRMP2-mediated cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%